2019
DOI: 10.5458/jag.jag.jag-2019_0011
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Low-Molecular-Mass Oil-gelling Agents: Synthesis and Physical Properties of 1,5-Anhydro-D-glucitol and 1,5-Anhydro-D-mannitol Protected with Saturated Linear Fatty Acids

Abstract: We have developed a novel low-molecular-mass oil-gelling agent that is electrically neutral, has no nitrogen atoms and consists only of cyclic sugar alcohols and saturated linear fatty acids. The cyclic sugar alcohols were 1,5-anhydro-D-glucitol (1,5-AG) and 1,5-anhydro-D-mannitol (1,5-AM) derived from starch via 1,5-anhydro-D-fructose. Various saturated linear fatty acids with 10 to 18 and 22 carbon atoms were introduced into all the hydroxy groups of 1,5-AG. Various saturated linear fatty acids with 13 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…and H-1ax), 3.59 (ddd, 1H, J 4,5 10.0 Hz, J 5,6′ 4.2 Hz, J 5,6 2.2 Hz, H-5), 4.08 (dd, 1H, J gem 12.4 Hz, J 5,6 2.1 Hz, H-6), 4.14 (dd, 1H, J gem 11.3 Hz, J 1eq,2 5.7 Hz, H-1 eq), 4.32 (dd, 1H, J gem 12.4 Hz, J 5,6′ 4.3 Hz, H-6′), 4.99−5.05 (m, 1H, H-2), 5.03 (t, 1H, J 3,4 = J 4,5 9.5 Hz, H-4), 5.18 (t, 1H, J 2,3 = J 3,4 9. 4 Hz, H-3), 5.82 (t, 1H, J NH,CH 2 5.6 Hz, NH), 5.99 (t, 1H, J NH,CH 2 5.8 Hz, NH), 6.21 (t, 1H, J NH,CH 2 5.8 Hz, NH), 6.22 (t, 1H, J NH,CH 2 5.9 Hz, NH); 13 C NMR (100 MHz, CDCl 3 ): δ 14.11 (C lipid -12), 22.69 (C lipid -11), 24.49 (C GABA -3), 24.52 (C GABA -3), 24.60 (C GABA -3), 24.68 (C GABA -3), 25.80 (C lipid -3), 25.81 (C lipid -3), 25.82 (C lipid -3), 29.35−29.67 ( 3.2.2. 1,5-Anhydro-2,3,4,6-tetra-O-{4-[(1-oxotetradecyl)amino]butanoyl}-D-glucitol (6: C 14 GABA-AG).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and H-1ax), 3.59 (ddd, 1H, J 4,5 10.0 Hz, J 5,6′ 4.2 Hz, J 5,6 2.2 Hz, H-5), 4.08 (dd, 1H, J gem 12.4 Hz, J 5,6 2.1 Hz, H-6), 4.14 (dd, 1H, J gem 11.3 Hz, J 1eq,2 5.7 Hz, H-1 eq), 4.32 (dd, 1H, J gem 12.4 Hz, J 5,6′ 4.3 Hz, H-6′), 4.99−5.05 (m, 1H, H-2), 5.03 (t, 1H, J 3,4 = J 4,5 9.5 Hz, H-4), 5.18 (t, 1H, J 2,3 = J 3,4 9. 4 Hz, H-3), 5.82 (t, 1H, J NH,CH 2 5.6 Hz, NH), 5.99 (t, 1H, J NH,CH 2 5.8 Hz, NH), 6.21 (t, 1H, J NH,CH 2 5.8 Hz, NH), 6.22 (t, 1H, J NH,CH 2 5.9 Hz, NH); 13 C NMR (100 MHz, CDCl 3 ): δ 14.11 (C lipid -12), 22.69 (C lipid -11), 24.49 (C GABA -3), 24.52 (C GABA -3), 24.60 (C GABA -3), 24.68 (C GABA -3), 25.80 (C lipid -3), 25.81 (C lipid -3), 25.82 (C lipid -3), 29.35−29.67 ( 3.2.2. 1,5-Anhydro-2,3,4,6-tetra-O-{4-[(1-oxotetradecyl)amino]butanoyl}-D-glucitol (6: C 14 GABA-AG).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, we have already reported that the hardness of C16AG gels increases up to 16 carbons and decreases with further extension from 16. 4 Unfortunately, the cause of these decreases…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Syntheses of acetylated derivatives: 2AC16AG, 3AC16AG, 4AC16AG, and 6AC16AG were obtained by acetylation of 1,5anhydro-d-glucitol tripalmitates 2OH16AG, 3OH16AG, 4OH16AG, and 6OH16AG (Scheme S1), which formed as byproducts in the synthesis of 1,5-anhydro-d-glucitol-2,3,4,6-O-tetrapalmitate (16AG) from 1,5-anhydro-d-glucitol, as reported previously. [15] 1,5-Anhydrod-glucitol-2,3,4,6-O-tetraacetate (ACAG) was synthesized by acetylation of 1,5-anhydro-d-glucitol.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we enzymatically synthesized 1,5-anhydro-d-glucitol, which does not have the 1-hydroxyl group, from starch as a raw material and esterified it with palmitoyl chloride to obtain 2,3,4,6-tetrapalmitoylated 1,5anhydro-d-glucitol derivative 16AG (Figure 1). [15] Interestingly, 16AG self-assembles into fibers and gelatinizes various kinds of organic solvents even though it has no conventional hydrogenbonding sites. In this study, we determined the structure of the self-assembled fibers and explored the gelation behavior and…”
Section: Introductionmentioning
confidence: 99%